2019
DOI: 10.4236/ojbd.2019.91004
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Profiles of Blood Transfusion Recipients at a Teaching and Referral Hospital in Kenya

Abstract: Background: Blood transfusion is an essential component of modern health care. It is required universally to manage various medical, surgical and obstetric conditions. Establishing the profiles of blood recipients would help in predicting the long term needs of blood transfusion as changing patterns of populations, diseases and health care will result in changing demands for blood and blood components. The objective of the study was to determine the pattern of blood use in terms of demographic and clinical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 20 publications
8
12
1
Order By: Relevance
“…This study also recorded that majority of recipients were from medical (48.2%) and surgical (22.4%) departments. Comparable results were reported in Kenya [ 60 ], Nigeria [ 23 ], Malawi (medical ward) [ 58 ], and Uganda (medical ward) [ 59 ], as most patients received transfusion therapy from medical and surgical wards. This could be due to high anemia prevalence, higher HIV and other infectious diseases burden, and surgical procedure hemorrhages resulting in the need for blood and blood product transfusions [ 60 ].…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…This study also recorded that majority of recipients were from medical (48.2%) and surgical (22.4%) departments. Comparable results were reported in Kenya [ 60 ], Nigeria [ 23 ], Malawi (medical ward) [ 58 ], and Uganda (medical ward) [ 59 ], as most patients received transfusion therapy from medical and surgical wards. This could be due to high anemia prevalence, higher HIV and other infectious diseases burden, and surgical procedure hemorrhages resulting in the need for blood and blood product transfusions [ 60 ].…”
Section: Discussionmentioning
confidence: 82%
“…Much of the transfusion recipients in this study were found to be females (65%) and younger cohorts (mean ±SD age of 27.47 ±15.28 years; median age of 26) of different clinical departments. Subsequently, similar studies in sub-Saharan Africa countries reported comparable results: 69.1% in Nigeria [ 23 ], 62.3 in Zimbabwe [ 56 ], Uganda female to male ratio (F:M) of 1.3 [ 57 ], 57.7% in Malawi [ 58 ], 58% in sub-Saharan Africa hospital [ 59 ], 55.2% in Kenya [ 60 ]. The low median age in this study indicates the structural distribution of the general population in sub-Saharan Africa regions which is mainly characterized by a higher proportion of younger people, as opposed to the aging population in developed countries [ 56 ].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations